Vessels, risks, and rules: Planning for safe shipping in Bering Strait. (January 2015) - Huntington, Henry P.; Daniel, Raychelle; Hartsig, Andrew; Harun, Kevin; Heiman, Marilyn; Meehan, Rosa; Noongwook, George; Pearson, Leslie; Prior-Parks, Melissa; Robards, Martin; Stetson, George
Abstract: Commercial vessel traffic through the Bering Strait is increasing. This region has high biological and cultural significance, to which commercial shipping poses several risks. For this environment, these risks include ship strikes of whales, noise disturbance, chronic pollution, and oil spills. Indigenous Chukchi, Iñupiaq, St. Lawrence Island Yupik, Siberian Yupik, and Yup'ik peoples may be affected by proximity between small hunting boats and large commercial vessels leading to swamping or collisions, through displacement of animals or impacts to food security from contaminants, and through loss of cultural heritage if archeological sites and other important places are disturbed by wakes or an increase in people spending time on shore. Several measures are available to govern shipping through the region, including shipping lanes, Areas to Be Avoided (ATBAs), speed restrictions, communications measures, reporting systems, emissions controls, oil spill prevention and preparedness and salvage, rescue tug capability, voyage and contingency planning, and improved charting. These measures can be implemented in various ways, unilaterally by the U.S. or Russia, bilaterally, or internationally through the International Maritime Organization (IMO). Regulatory measures can be established as voluntary measures or as mandatory measures. No single measure will address all risks, but the framework presented herein may serve as a means of identifying what needs to be done and evaluating whether the goal of safe shipping has been achieved. Highlights: The Bering Strait is an area of great biological and cultural significance. Increasing commercial ship traffic presents environmental and cultural risks. Many mitigation measures are available to reduce risks. Implementation of measures can be done in stages, nationally and internationally. Managing commercial vessel traffic presents a marine policy challenge.